European partnership on radioactive waste management - Théodon Louise; Bruggeman Christophe; Göbel Astrid; Holt Erika (EPJ Nuclear Sciences & Technologies)
The European Commission supports a co-funded European Partnership on radioactive waste management within the EURATOM Work Programme for 2023-2025. This initiative, known as EURAD-2, aims to continue and merge the efforts of the EURAD Programme and the PREDIS project, building on their successes and lessons learned. EURAD-2 addresses the European Union’s 3.5 million m3 radioactive waste inventory with a holistic approach, targeting the whole waste management chain from cradle to grave, up until its final disposal in surface, shallow, and deep geological facilities. As a co-funded Partnership, it supports Member States in meeting the Research, Development and Demonstration requirements of the Waste Directive 2011/70. The programme includes diverse participation, with 51 beneficiary organisations and 69 Affiliated Entities from 21 Member States, funded at 60% by the European Commission and 40% by the participating Member States. Furthermore, it welcomes participation from associated countries and interacts proactively with international organisations such as NEA and IAEA. The EURAD-2 work plan addresses strategic aspects identified in the updated EURAD Strategic Research and Knowledge Management Agenda. To this end, the Partnership employs different instruments (different types of work packages): research and development – performing cutting-edge science and technology research and innovation; Strategic Studies – shorter-term transversal collaborative actions bringing together relevant actors and addressing emerging needs; Knowledge Management – supporting the transfer of knowledge between different programmes and between generations. EURAD-2 aspires to contribute as one of the leading European platforms for radioactive waste management competence, know-how, and capabilities, supporting scientific excellence and driving innovation in research and technology for its end users. It aims to be a central hub for training new experts and facilitating high-visibility position papers on emerging topics, further establishing the European Union as the forerunner in safe, long-term radioactive waste management.